Management of Arteriovenous Fistula After Successful Kidney Transplantation in Long-Term Follow-Up - Janeckova, Jana; Bachleda, Petr; Utikal, Petr; Orsag, Jirir (Transplant international : official journal of the European Society for Organ Transplantation, 2024)
Arteriovenous fistula (AVF) is the best method of vascular access for hemodialysis. This approach can lead to several complications, such as hyperkinetic heart failure due to a hyperfunctional AVF or dilatation of the feeding artery. These are late complications, especially in patients after a successful kidney transplantation. An observational study was performed focusing on patients more than 12 months after kidney transplantation. The AVF was evaluated by ultrasound and, if the outflow exceeded 1.5 L/min, an echocardiogram was performed. Surgical management was indicated if the cardiac index was higher than 3.9 L/min/m2 or upon finding a brachial artery aneurysm. A total of 208 post- kidney transplantation patients were examined over a 3-year period, of which 46 subjects (22.11%) had hyperfunctional AVF and 34 cases (16.34%) of feeding artery dilatation were determined. In total, 40 AVF flow reduction and 6 AVF ligation procedures were performed. The median AVF flow before and after the reduction was 2955 mL/min and 1060 mL/min, respectively. Primary patency after flow reduction was 88.3% at 12 months. Late AVF complications in patients following kidney transplantation are quite common. It is necessary to create a screening program to monitor AVFs in these patients.
Keywords: echokardiografie; dospělí; Female; Renal Dialysis; dialýza ledvin; Adult; ženské pohlaví; arteria brachialis; průchodnost cév; lidé; Arteriovenous Shunt, Surgical; pooperační komplikace; následné studie; Echocardiography; transplantace ledvin; Kidney Transplantation; Male; Follow-Up Studies; Postoperative Complications; Aged; arteriovenózní zkrat; Vascular Patency; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Brachial Artery; Humans